Groundwater Resources in Local Development Strategies: Case of Izmir - Velibeyoğlu, Koray; Yazdani, Hamidreza; Velibeyoğlu, Koray; Baba, Alper; Baba, Alper (International Water Association, 2017)
Rural socio economic development has gained utmost importance in Turkish Metropolitan Municipalities within the frame of recent legal changes extending boundaries towards their peripheral areas. With this regard, Ġzmir Metropolitan Municipality has completed series of local development strategies aiming at the sustainable development of the city‘s rural hinterland. For three fertile sub region of Izmir, namely as Yarımada, Gediz Bakırçay and Küçük Menderes, local development strategies were prepared consecutively. In the framework of local development strategies; agriculture, tourism, settlement pattern and culture, local innovation and entrepreneurship, and environmental issues and water resources were examined as project themes. Among them, water resources has utmost important since the local development of whole sectors are largely dependent on them. Therefore, local development strategies have underlined the reality of river basins and potentials and limitations on groundwater resources due to the fact that surface waters have already been contaminated.
IWA 2nd Regional Symposium on water, wastewater and environment, 22-24 March 2017, Cesme, İzmir
Keywords: Groundwater; Local development; Water resources; GIS